Contrast-enhanced transthoracic echocardiography applied in evaluation of pulmonary right-to-left shunt: A preliminary study. (September 2018) - Feng, Cheng; Luo, Tingting; Luo, Yongfang; Zhao, Ningbo; Huang, Kun; Xiao, Chang
Highlights: This research aimed to investigate the detection rate of patent foramen ovale-right to left shunt and/or pulmonary-right to left shunt via contrast-enhanced transthoracic echocardiography in healthy participants, patients suffering from cryptogenic stroke and migraine with aura. And the conclusions is of great significance for clinical practice. Previous studies only focused on PFO-RLS, in terms of RLS related diseases. Recently, 25–50 μmol physiological arteriovenous anastomotic branches or channels are commonly found in healthy human lungs, indicating P-RLS is not only derived from PAVMs. Although most studies have demonstrated that the RLS incidence rates of cryptogenic stroke and migraine aura are relatively higher, when compared with healthy populations, numerous issues still remain controversial. This finding can greatly contribute to physicians. Abstract: Objective: To investigate the detection rate of patent foramen ovale-right to left shunt (PFO-RLS) and/or pulmonary-right to left shunt (P-RLS) via contrast-enhanced transthoracic echocardiography (c-TTE) in healthy participants, patients suffering from cryptogenic stroke and migraine with aura. Methods: Initially, 20 healthy volunteers, 21 cases with cryptogenic stroke, and 18 cases with migraine aura were randomly selected, and all of them received c-TTE and transesophageal echocardiography (TEE) examinations. First of all, 0.9% sodium chloride solution was rapidly injected into upper extremiry vein, when these volunteers and patients were at rest or following a Valsalva maneuver with 40 mm Hg pressure exerted against a manometer. Secondly, c-TTE detection was carried out in order to distinguish PFO-RLS and P-RLS and make semi-quantitative classification of RLS from many different sources, according to the occurrence and duration time of microvesicles in left atrial after the developing of left atrium. In terms of c-TTE analyses, RLS could be diagnosed when micro bubbles were visualized in transition from the right atrium to the left atrium. Particularly, a small amounts of RLS was 1 level, indicating 1–10 microvesicles per frame could be seen in left atrium, moderate amounts of RLS was 2 level, indicating 11–30 microvesicles per frame could be seen in left atrium, and a large amounts of RLS was 3 level, indicating more than 30 microvesicles per frame, or the left atrium is filled with micro vesicles. Results: A total of 20 healthy adult volunteers were identified into this research. RLS was detected in 7 cases, according to c-TTE method (7/20, 35%). In detail, 3 participants suffered from PFO-RLS and P-RSL (3/20, 15%) simultaneously, 5 cases suffered from PFO-RLS (5/20, 25%), and 5 cases suffered from P-RLS (5/20, 25%). Among 21 patients with cryptogenic stroke, RLS was detected in 14 cases, according to cTTE method (14/20, 67%), and then compared with healthy participants group, the difference between them was significant (χ 2 = 4.11, P = 0.04). Specifically, 2 participants suffered from PFO-RLS and P-RSL (2/21, 9.5%), 11 cases suffered from PFO-RLS (11/21, 52.4%), and 5 cases suffered from P-RLS (5/21, 23.8%). Among 21 patients suffering from migraine with aura, RLS was detected in 13 cases, according to c-TTE method (13/18, 72%), and then compared with healthy participants group, the difference of detection rate between them was significant (χ 2 = 5.2, P = 0.02). In detail, 3 participants suffered from PFO-RLS and P-RSL (3/18, 16.7%), 8 cases suffered from PFO-RLS (8/18, 44.4%), and 8 cases suffered from P-RLS (8/18, 44.4%). In addition, the grading of PFO-RLS in patients suffering from cryptogenic stroke and migraine with aura was mostly grade 2–grade 3. On the contrary, the grading of PFO-RLS in healthy adult volunteers was mostly grade 1–2. Besides, the semi-quantitative grading of P-RLS in each group was mostly grade 1 to grade 2, and difference between healthy volunteer group and cryptogenic stroke group was significant (Z = −2.77, P = 0.006). Conclusion: P-RLS with lower semiquantitative grade is common in healthy individuals, patients with cryptogenic stroke and migraine aura. And P-RLS can be considered as a significant influencing factor in the pathogenesis of migraine with aura.